Hypertriglyceridemia – when should a specialist be contacted? - Broncel, Marlena (Lekarz POZ, 2018)
Mild or moderate hypertriglyceridemia (HTG) (serum triglyceride concentration up to 880 mg/dl; 10 mmol/l) may increase cardiovascular risk, whereas severe HTG (serum triglyceride concentration above 880 mg/dl; 10 mmol/l) increases the risk of acute pancreatitis. HTG requires careful diagnosis, exclusion and correction of the causes of secondary disorders. Depending on the severity of HTG, appropriate lifestyle changes and pharmacological treatment should be implemented.